Cellulose-based resin composition and molded article using the same
By adding an appropriate amount of trifluorophenol phosphate and anti-drip to the resin composition, the shortcomings of the existing resin composition in terms of fire protection and designability are solved, and high fire protection and high design resin molded products are achieved.
Patent Information
- Application Number
- JP2023538635
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-29
- Filing Date
- 2022-07-29
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-07-29
AI Technical Summary
The existing cellular hyperaldehyde resin compositions have shortcomings in fire protection and design, and it is difficult to achieve high fire protection and design at the same time.
The resin composition containing cell hyalic acid, trifluorophenol phosphate and anti-drip agent is used to ensure that the content of trifluorophenol phosphate is between 25% and 30% and the content of anti-drip agent is between 0.01% and 1% to improve fire protection and designability.
High fire protection and high design properties are achieved, and resin molded products with high mechanical strength and good transparency can be formed.
Smart Images

Figure 0007670388000001 
Figure 0007670388000002 
Figure 0007670388000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cellulose-based resin composition and a molded article using the same. [Background technology]
[0002] Bioplastics made from plant components can contribute to combating oil depletion and global warming, and so they are beginning to be used in durable products such as electronic devices and automobiles, in addition to general products such as packaging, containers, and textiles.
[0003] Conventional bioplastics, such as polylactic acid, polyhydroxyalkanoates, and modified starch, are all made from starch-based materials, i.e., edible parts of plants. Therefore, due to concerns about future food shortages, there is a demand for the development of new bioplastics made from inedible parts of plants.
[0004] A typical example of the raw material for the inedible parts is cellulose, a major component of wood and plants, and various bioplastics using this have been developed and commercialized.
[0005] These plant-derived resins are generally flammable, so flame retardant measures are necessary when they are used in applications that require a high level of flame retardancy, such as housings for home appliances and office automation equipment. In particular, when using resin compositions made from plant-derived resins for the housings of electrical appliances, they need to satisfy flame retardant standards, including the UL94 standard.
[0006] In order to improve flame retardancy, a resin composition containing a flame retardant has been studied. For example, Patent Document 1 discloses a resin composition containing a polylactic acid resin, a cellulose ester, an aromatic polycarbonate resin, a compatibilizer, and a flame retardant. Patent Document 2 discloses a resin composition containing a cellulose ester and a cyclic phosphorus compound having a specific structure. Patent Document 3 discloses a resin composition containing a cellulose ester, a polycarbonate resin, a plasticizer containing a polymer of a specific number average molecular weight, and a phosphorus-containing flame retardant. Patent Document 4 discloses a cellulose ester resin composition containing a cellulose ester resin, a phosphoric acid ester having a specific structure, and polytetrafluoroethylene in a specific content.
[0007] On the other hand, in recent years, there has been a demand for resin molded products that have a high-quality appearance and are highly designed even without painting. If resin molded products are not painted, it is possible to reduce the emission of volatile organic compounds (VOCs) and the painting costs during production, and it is also possible to solve the problem of poor appearance of the resulting molded products due to peeling and deterioration of the paint film. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2006-111858 A [Patent Document 2] JP 2011-241236 A [Patent Document 3] JP 2011-225841 A [Patent Document 4] Patent No. 6239504 Summary of the Invention [Problem to be solved by the invention]
[0009] However, with regard to the resin compositions described in Patent Documents 1 to 4, investigations into cellulose-based resin compositions having excellent flame retardancy and designability have been insufficient.
[0010] An object of the present embodiment is to provide a cellulose-based resin composition capable of forming a molded article having excellent flame retardancy and excellent designability, and a molded article formed using the same. [Means for solving the problem]
[0011] One aspect of the present embodiment relates to the following.
[0012] Component (A): Cellulose acetate, Component (B): one or more phosphate esters selected from the group consisting of triphenyl phosphate, triethyl phosphate, tributyl phosphate, and tricresyl phosphate; Component (C): Anti-drip agent, Including, The content of component (B) is 25% by mass or more and 30% by mass or less relative to 100% by mass of the total content of components (A) and (B), A cellulose-based resin composition, wherein the content of component (C) is 0.01% by mass or more and 1% by mass or less, relative to 100% by mass of the total content of components (A), (B) and (C). Effect of the Invention
[0013] According to the present embodiment, it is possible to provide a cellulose-based resin composition capable of forming a molded article having high flame retardancy and excellent design, and a molded article molded using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] One aspect of the cellulose-based resin composition of the present embodiment (also simply referred to as a "resin composition" or a "cellulose acetate resin composition") is Component (A): Cellulose acetate, Component (B): one or more phosphate esters selected from the group consisting of triphenyl phosphate, triethyl phosphate, tributyl phosphate, and tricresyl phosphate; Component (C): Anti-drip agent, Including, The content of component (B) is 25% by mass or more and 30% by mass or less relative to 100% by mass of the total content of components (A) and (B), The content of component (C) is 0.01% by mass or more and 1% by mass or less relative to 100% by mass of the total content of components (A), (B) and (C).
[0015] The resin composition of the present embodiment is capable of forming a molded article having high flame retardancy and processing stability, and excellent design. Each component will be described below.
[0016] <Component (A)> The cellulose-based resin composition of the present embodiment contains cellulose acetate (also referred to as "CA") as component (A). As the cellulose acetate, one in which acetyl groups have been introduced into at least a portion of the hydroxyl groups of cellulose as a raw material can be used.
[0017] Cellulose is a linear polymer formed by polymerization of β-D-glucose molecules (β-D-glucopyranose) represented by the following formula (1) via β(1→4) glycosidic bonds. Each glucose unit constituting cellulose has three hydroxyl groups (n in the formula is a natural number). In this embodiment, acetyl groups are introduced into such cellulose by utilizing these hydroxyl groups.
[0018] [ka]
[0019] Cellulose is the main component of plants and can be obtained by separating and treating other components such as lignin from plants. In addition to those obtained in this way, cotton (e.g., cotton linters) and pulp (e.g., wood pulp) with a high cellulose content can be used as is or after purification. The shape, size and form of cellulose or its derivatives used as raw materials are preferably in the form of powder with an appropriate particle size and shape in terms of reactivity, solid-liquid separation and ease of handling. Although not limited, for example, fibrous or powdery materials with a diameter of 1 to 100 μm (preferably 10 to 50 μm) and a length of 10 μm to 100 mm (preferably 100 μm to 10 mm) can be used.
[0020] The degree of polymerization of cellulose, expressed as the glucose polymerization degree (average polymerization degree), is preferably in the range of 50 to 5000, more preferably 100 to 3000, and even more preferably 100 to 1000. If the degree of polymerization is too low, the strength, heat resistance, etc. of the produced resin may be insufficient. Conversely, if the degree of polymerization is too high, the melt viscosity of the produced resin may become too high, causing problems in molding.
[0021] The cellulose acetate in this embodiment can be obtained by utilizing the hydroxyl groups of cellulose and introducing acetyl groups.
[0022] The acetyl group can be introduced by reacting a hydroxy group in cellulose with an acylating agent. The acetyl group corresponds to an organic group portion introduced in place of a hydrogen atom of a hydroxy group in cellulose. The acylating agent is a compound having at least one functional group capable of reacting with a hydroxy group in cellulose, and examples of the acylating agent include compounds having a carboxyl group, a carboxylic acid halide group, and a carboxylic acid anhydride group. Specific examples include aliphatic monocarboxylic acids (acetic acid), their acid halides, and their acid anhydrides (acetic anhydride).
[0023] The average number of acetyl groups introduced per glucose unit of cellulose (DS AC) (acetyl group introduction ratio), i.e., the average number of hydroxyl groups substituted with acetyl groups per glucose unit (hydroxyl group substitution degree), can be set in the range of 0.1 to 3.0. In order to fully obtain the effect of introducing acetyl groups, particularly from the viewpoints of water resistance, fluidity, etc., DS AC is preferably 2.0 or more, more preferably 2.2 or more, and even more preferably 2.4 or more. From the viewpoint of obtaining the effect of introducing an acetyl group while fully obtaining the effect of other groups (hydroxyl group, etc.), DS AC is preferably 2.9 or less, more preferably 2.8 or less.
[0024] By introducing the above-mentioned acetyl group into cellulose, the intermolecular force (intermolecular bond) of cellulose can be reduced, and the plasticity of the cellulose acetate resin composition can be improved.
[0025] The more the residual amount of hydroxyl groups, the greater the maximum strength and heat resistance of the cellulose acetate resin composition, but the greater the water absorption. On the other hand, the higher the conversion rate (degree of substitution) of the hydroxyl groups, the lower the water absorption and the greater the plasticity and breaking strain, but the lower the maximum strength and heat resistance. Taking these trends into consideration, the conversion rate of the hydroxyl groups can be appropriately set.
[0026] The average number of remaining hydroxyl groups per glucose unit of cellulose acetate (residual hydroxyl degree) can be set in the range of 0 to 2.9. Hydroxy groups may remain from the viewpoint of the maximum strength, heat resistance, etc. of the cellulose acetate resin composition, and for example, the residual hydroxyl degree may be 0.01 or more, and even 0.1 or more. In particular, from the viewpoint of the fluidity of the cellulose acetate resin composition, the residual hydroxyl degree of the final product cellulose acetate is preferably 1.0 or less, more preferably 0.8 or less, and even more preferably 0.6 or less.
[0027] The molecular weight of cellulose acetate is preferably in the range of 10,000 to 400,000, more preferably in the range of 50,000 to 350,000, even more preferably in the range of 100,000 to 300,000, and even more preferably in the range of 150,000 to 250,000. If the molecular weight is too large, the fluidity of the cellulose acetate resin composition is reduced, making processing difficult, and uniform mixing may be difficult. Conversely, if the molecular weight is too small, physical properties such as impact resistance of the cellulose acetate resin composition may be reduced. This weight average molecular weight can be determined by gel permeation chromatography (GPC) (commercially available standard polystyrene can be used as a standard sample).
[0028] <Ingredient (B)> The cellulose-based resin composition of the present embodiment contains, as component (B), one or more phosphate esters selected from the group consisting of triphenyl phosphate (also referred to as "TPP"), triethyl phosphate, tributyl phosphate, and tricresyl phosphate. Component (B) functions as a flame retardant and plasticizer, and can impart flame retardancy and moldability to the resin composition. In addition, these specific phosphate esters are highly compatible with cellulose acetate, and do not become cloudy even when mixed with cellulose acetate, resulting in a highly transparent resin composition.
[0029] In one aspect of this embodiment, component (B) preferably contains triphenyl phosphate (TPP). In one aspect, the content of TPP in the total amount of component (B) is preferably 80 mass% or more, more preferably 90 mass% or more, and may be 100 mass%. TPP is difficult to volatilize and has high compatibility with component (A). In addition, the use of TPP allows the formation of a resin composition with high mechanical strength.
[0030] The component (B) may be used alone or in combination of two or more kinds.
[0031] In one aspect of the present embodiment, from the viewpoint of obtaining a molded article with excellent design, it is preferable that the content of the phosphate ester (referred to as "phosphate ester (b')") having low compatibility with component (A) is small. Examples of the phosphate ester (b') include those represented by the following formula:
[0032] [ka] A compound represented by the formula:
[0033] [ka] A compound represented by the formula:
[0034] [ka] and condensed phosphate compounds such as a compound represented by the formula: cresyl di-2,6-xylenyl phosphate, [(CH3)2C6H3O]2P(O)OC6H4OP(O)[OC6H3(CH3)2]2, etc. The content of the phosphate ester (b') in the resin composition is preferably 3 mass% or less, more preferably 1 mass% or less, and even more preferably 0 mass%.
[0035] In the cellulose-based resin composition, the content of component (A) is preferably 70% by mass or more, more preferably 72% by mass or more, and preferably 75% by mass or less, relative to 100% by mass of the total content of components (A) and (B).
[0036] In the cellulose-based resin composition, the content of component (B) is preferably 25% by mass or more, and preferably 30% by mass or less, more preferably 28% by mass or less, based on the total content of component (A) and component (B) being 100% by mass. When the content of component (B) is within this range, the resin composition can be made to have excellent processing stability and flame retardancy, and to suppress bleeding out. If the content of component (B) is too high, bleeding may occur. On the other hand, if the content of component (B) is too low, processing stability and flame retardancy may become insufficient. Processing stability can be evaluated by the method described in the examples.
[0037] The total content of component (A) and component (B) relative to 100% by mass of the total amount of the cellulose-based resin composition is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, still more preferably 95% by mass or more, and is preferably less than 99.8% by mass, more preferably 99.5% by mass or less, even more preferably 99% by mass or less, and still more preferably 98% by mass or less.
[0038] <Ingredient (C)> The cellulose-based resin composition of the present embodiment contains an anti-drip agent as component (C). By containing component (C), the cellulose-based resin composition shrinks when heated, and the molten resin can be prevented from dripping (drip) and spreading the combustion. As the anti-drip agent, a fluorine-based anti-drip agent (fluorine-containing polymer) is preferable, and it is more preferable to contain a fluorine-containing polymer that forms a fiber structure (fibril structure) in the resin composition. By blending a fluorine-containing polymer, the effect of suppressing the drip phenomenon during combustion can be improved.
[0039] Examples of the drip prevention agent include fluororesins such as polytetrafluoroethylene (PTFE), tetrafluoroethylene copolymers (e.g., tetrafluoroethylene / hexafluoropropylene copolymers, etc.), resins in which polytetrafluoroethylene is acrylic-modified, polyvinylidene fluoride, and polyhexafluoropropylene, and perfluoroalkanesulfonic acid alkali metal salt compounds or perfluoroalkanesulfonic acid alkaline earth metal salts such as sodium perfluoromethanesulfonate, potassium perfluoro-n-butanesulfonate, potassium perfluoro-t-butanesulfonate, sodium perfluorooctane sulfonate, and calcium perfluoro-2-ethylhexanesulfonate. In addition, various forms of fluoropolymers such as fine powder fluoropolymers, aqueous dispersions of fluoropolymers, mixtures of powder fluoropolymers and acrylonitrile-styrene copolymers, and mixtures of powder fluoropolymers and polymethyl methacrylate can also be used as the fluoropolymer. Similarly, silicone compounds such as silicone rubbers and layered silicates such as talc may be blended as other drip prevention agents. These may be used alone or in combination of two or more.
[0040] Among these, a fluorine-based drip prevention agent having fibril forming ability is preferred, and polytetrafluoroethylene (PTFE) is particularly preferred. The molecular weight of the fluorine-based drip prevention agent (particularly PTFE) is preferably 1 to 10 million, more preferably 2 to 9 million, in terms of number average molecular weight calculated from standard specific gravity. Such PTFE may be in the form of a solid or an aqueous dispersion. In one embodiment, the content of PTFE in the total amount of component (C) is preferably 80 mass% or more, more preferably 90 mass% or more, and may be 100 mass%.
[0041] In the cellulose-based resin composition, the content of component (C) is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, more preferably 0.2% by mass or more, even more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, and is preferably 1.0% by mass or less, more preferably 0.8% by mass or less, based on the total content of component (A), component (B) and component (C) (100% by mass). If the content of component (C) is too high, the processing stability may be reduced, and the design properties such as transparency may be reduced. On the other hand, if the content of component (C) is too low, the flame retardancy may be insufficient.
[0042] The cellulose-based resin composition according to the present embodiment may contain other components within a range that does not impair the desired appearance or properties when molded into a product. In one embodiment, for example, the total amount of components (A), (B), and (C) is preferably set to a range of 75 to 100 mass% based on the entire cellulose-based resin composition, more preferably 80 mass% or more, more preferably 90 mass% or more, more preferably 95 mass% or more, more preferably 98 mass% or more, and even more preferably 99 mass% or more.
[0043] The resin composition of the present embodiment may contain a colorant as described below, but in an embodiment that does not contain a colorant, it is preferable that the resin composition has high transparency. The resin composition may be colorless or colored, but is preferably colorless and transparent. High transparency results in good color development when a colorant or the like is added, and a molded product with a high-quality appearance, i.e., excellent design, can be formed.
[0044] In one aspect of this embodiment, the haze value of a molded article having a thickness of 500 μm that is formed from a resin composition that does not contain a colorant is preferably 35% or less, and more preferably 10% or less.
[0045] The resin composition of the present embodiment may contain a colorant in addition to the components (A), (B), and (C).
[0046] (Coloring agent) In one embodiment, the cellulose-based resin composition of the present embodiment may include a colorant, such as a black colorant.
[0047] The content of the colorant such as a black colorant is not limited, but can be set in the range of 0.01 to 10 phr (meaning 0.01 to 10 parts by mass per 100 parts by mass of the total mass of the components other than the colorant in the cellulose-based resin composition. The standard for the content of the colorant is the same below) relative to the total mass of the components other than the colorant. From the viewpoint of obtaining a sufficient coloring effect, the content of the colorant is preferably 0.05 phr or more, preferably 0.09 phr or more, and preferably 0.1 phr or more, relative to the total mass of the components other than the colorant. From the viewpoint of suppressing the excess amount of the colorant while obtaining a sufficient coloring effect, it is preferably 5 phr or less, more preferably 3 phr or less, and even more preferably 2 phr or less.
[0048] From the viewpoint of appearance such as glossiness, the content of the colorant is preferably 1 phr or less, more preferably 0.3 phr or less, further preferably 0.2 phr or less, and particularly preferably 0.1 phr or less.
[0049] As the black colorant, carbon black is preferred.
[0050] The average particle size of the carbon black is preferably 1 to 20 nm, more preferably 5 to 20 nm, and even more preferably 8 to 18 nm. The smaller the average particle size, the lower the brightness of the molded product, and the more likely it is that a high-quality black (jet black) appearance will be obtained. Conversely, the larger the average particle size, the higher the dispersibility. From these viewpoints, it is preferable to use carbon black with a particle size within the above range.
[0051] This average particle size is the arithmetic mean particle size determined by observing carbon black particles under an electron microscope.
[0052] In one embodiment, the specific surface area of the carbon black is, but not limited to, 140 m 2 / g or more is preferable, and 180m 2 / g or more is more preferable. 2 / g or less can be used, and 2 / g or less, and even 500m 2 / g or less can be used. In terms of the relationship between particle size and specific surface area, the smaller the particle size, the larger the specific surface area. From the viewpoints of the brightness and appearance of the molded product and the dispersibility of the particles, it is preferable to use carbon black with a BET specific surface area within the above range. This specific surface area is the BET specific surface area (JISK6217) calculated from the nitrogen adsorption amount using the S-BET formula.
[0053] In one embodiment, the carbon black is preferably acidic, specifically, preferably pH 5 or less, more preferably pH 4 or less, and even more preferably pH 3.5 or less. By using such acidic (low pH) carbon black, the brightness of the molded article can be reduced. For example, carbon black having a pH of preferably 2.5 to 4, more preferably 2.5 to 3.5, can be suitably used.
[0054] This pH value was measured using a glass electrode pH meter on a mixture of carbon black and distilled water. The specific measurement method is as follows: 100 ml of boiled and degassed pure water is added to 10 g of sample, boiled on a hot plate for 15 minutes, cooled to room temperature, the supernatant liquid is removed, and the pH of the resulting muddy substance is measured using a glass electrode pH meter.
[0055] It is believed that the affinity between the acidic groups (e.g., carboxylic acid groups) on the surface of such acidic carbon black and the polar groups (e.g., hydroxyl groups) of cellulose acetate is improved by interaction or bonding, resulting in high dispersion of the carbon black and contributing to a decrease in brightness.
[0056] As colorants other than the black colorant, organic or inorganic pigments or dyes can be used.
[0057] The resin composition may contain, as other components, additives generally used in ordinary molding resin materials, within the scope of the present embodiment. Examples of such additives include phenolic or phosphorus-based antioxidants, light stabilizers, ultraviolet absorbers, antistatic agents, antibacterial and antifungal agents, fillers, etc. In particular, the resin composition may contain additives generally used in ordinary cellulose-based resins.
[0058] In the resin composition of the present embodiment, an inorganic or organic granular or fibrous filler can be added as necessary while taking into consideration maintaining transparency. By adding a filler, the strength and rigidity can be further improved. Examples of fillers include mineral particles (talc, mica, calcined silica earth, kaolin, sericite, bentonite, smectite, clay, silica, quartz powder, glass beads, glass powder, glass flakes, milled fiber, wollastonite (or wollastonite), etc.), boron-containing compounds (boron nitride, boron carbide, titanium boride, etc.), metal carbonates (magnesium carbonate, heavy calcium carbonate, light calcium carbonate, etc.), metal silicates (calcium silicate, aluminum silicate, magnesium silicate, magnesium aluminosilicate, etc.), metal oxides (magnesium oxide, etc.), metal sulfates (calcium sulfate, barium sulfate, etc.), metal carbides (silicon carbide, aluminum carbide, titanium carbide, etc.), metal nitrides (aluminum nitride, silicon nitride, titanium nitride, etc.), white carbon, and various metal foils. Examples of fibrous fillers include organic fibers (natural fibers, paper, etc.), inorganic fibers (glass fibers, asbestos fibers, carbon fibers, silica fibers, silica-alumina fibers, wollastonite, zirconia fibers, potassium titanate fibers, etc.), metal fibers, etc. These fillers can be used alone or in combination of two or more.
[0059] In one aspect of this embodiment, the resin composition may contain glass fibers. The strength of the molded body is improved by the resin composition containing glass fibers. The glass fibers are not particularly limited, but the fiber length of the glass fibers before melt-kneading is preferably 0.5 mm or more, and preferably 30 mm or less, more preferably 10 mm or less. The cross-sectional shape of the glass fibers is not particularly limited, and examples thereof include circular, elliptical, oval, and non-circular. The fiber diameter of the glass fibers may be, for example, 3 to 20 μm when the cross-sectional area is converted into a perfect circle. In one aspect of this embodiment, the content of the glass fibers relative to the total mass of the resin composition may be 0 mass%, but is, for example, preferably 0.5 mass% or more, more preferably 1 mass% or more, and even more preferably 3 mass% or more, and is also preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 8 mass% or less.
[0060] In one aspect, the resin composition of the present embodiment preferably has a low content of polylactic acid resin and aromatic polycarbonate resin. If the resin composition contains polylactic acid resin or aromatic polycarbonate resin, the compatibility with cellulose acetate is low, so that cloudiness occurs, and it becomes difficult to obtain a molded product with excellent design. The content of these components is preferably 3% by mass or less, more preferably 1% by mass or less, and even more preferably 0% by mass, based on the total mass of the resin composition.
[0061] In one aspect, the resin composition of the present embodiment preferably contains a small amount of inorganic flame retardant such as metal hydroxide (aluminum hydroxide, calcium hydroxide, magnesium hydroxide, etc.). If the resin composition contains an inorganic flame retardant, it becomes cloudy, making it difficult to obtain a molded product with excellent design. In addition, if the content of the inorganic flame retardant is small, it becomes easier to obtain a molded product with high impact resistance. The content of the inorganic flame retardant is preferably 3% by mass or less, more preferably 1% by mass or less, and even more preferably 0% by mass, based on the total mass of the resin composition.
[0062] <Method of producing cellulose-based resin composition> The method for producing the cellulose-based resin composition is not particularly limited, and for example, the cellulose-based resin composition can be obtained by melt-mixing the components (A), (B) and (C) with other components as necessary using a normal mixer. As the mixer, for example, a compounding device such as a tumbler mixer, a ribbon blender, a single-screw or multi-screw mixing extruder, a kneading kneader, or a kneading roll can be used. After melt mixing, the mixture can be granulated into an appropriate shape as necessary, for example, pelletized using a pelletizer.
[0063] <Molded body> The molded article formed using the cellulose resin composition according to the present embodiment can be formed into a desired shape by a normal molding method, and the shape and thickness of the molded article are not limited. From the viewpoint of the strength of the molded article, the thickness is preferably 0.5 mm or more, more preferably 0.8 mm or more. Furthermore, from the viewpoint of flame retardancy, the thickness is preferably 1.0 mm or more, more preferably 1.6 mm or more, more preferably 2.0 mm or more, and even more preferably 3.2 mm or more. On the other hand, the upper limit of the thickness of the molded article is not particularly limited, and can be appropriately set according to the required shape, strength, etc., but sufficient physical properties can be obtained even if the thickness is set to, for example, 10 mm or less, or even 5 mm or less.
[0064] Since each component is distributed throughout the molded body of this embodiment (in any direction including the thickness direction), a high-quality appearance can be obtained in any shape without the need for paint, decorative film, etc.
[0065] The cellulose-based resin composition according to the present embodiment can be molded into a molded article according to the intended use by a common molding method such as injection molding, injection compression molding, extrusion molding, or hot press molding.
[0066] The molded article formed using the cellulose-based resin composition according to the present embodiment has excellent flame retardancy and designability, and can be applied to housings, exteriors, decorative panels, and decorative sheets, and can be used in place of components used in, for example, electronic devices, home appliances, building materials, furniture, and automobiles. For example, it can be used in housings and exterior parts of electronic devices and home appliances, interior components of building materials, and interior materials of automobiles.
[0067] According to this embodiment, it is possible to provide products such as electronic devices, home appliances, automobiles, building materials, and furniture, which include a molded article formed using the resin composition according to the present invention.
[0068] Applications for electronic devices and home appliances include housings for computers, landlines, mobile phones, smartphones, tablets, POS terminals, routers, projectors, speakers, lighting equipment, copiers, multi-function printers, calculators, remote controls, refrigerators, washing machines, humidifiers, dehumidifiers, video recorders / players, vacuum cleaners, air conditioners, rice cookers, electric shavers, electric toothbrushes, dishwashers, broadcasting equipment, clock faces and exteriors, and cases for mobile devices such as smartphones.
[0069] Automotive applications include interior instrument panels, dashboards, cup holders, door trim, arm rests, door handles, door locks, steering wheels, brake levers, ventilators, shift levers, and the like. EXAMPLES
[0070] The present invention will be described in more detail below with reference to specific examples, but the present invention is not limited to these.
[0071] The components used in producing the resin compositions of the Examples and Comparative Examples are shown below.
[0072] <Component (A)> (a1) Cellulose acetate (CA) (manufactured by Daicel Corporation, product name: L-50, acetyl group introduction ratio (substitution degree) DS = 2.4, acetylation degree 55%, polymerization degree based on 6% viscosity 180) <Ingredient (B)> (b1) Triphenyl phosphate (TPP) (manufactured by Daihachi Chemical Industry Co., Ltd., product name: TPP)
[0073] <Phosphate ester (b')> (b1') the following formula:
[0074] [ka] A compound represented by the formula (manufactured by ADEKA Corporation, product name: ADK STAB FP-600) (b2') the following formula:
[0075] [ka] A compound represented by the formula (manufactured by ADEKA Corporation, product name: Adeka STAB FP-900L) (b3') the following formula:
[0076] [ka] A compound represented by the formula (manufactured by ADEKA Corporation, product name: ADK STAB PFR)
[0077] (b4') Cresyl di-2,6-xylenyl phosphate (manufactured by Daihachi Chemical Industry Co., Ltd., product name: PX-110) (b5') [(CH3)2C6H3O]2P(O)OC6H4OP(O)[OC6H3(CH3)2]2 (manufactured by Daihachi Chemical Industry Co., Ltd., product name: PX-200)
[0078] <Component (C)> (c1) Polytetrafluoroethylene (PTFE) (manufactured by Daikin Industries, Ltd., product name: Polyflon MPA FA-500H)
[0079] <Coloring agent> (d1) Carbon black (acidic carbon black (average particle size: 13 nm, pH 3) (manufactured by Mitsubishi Chemical Corporation, product name: Mitsubishi Carbon Black #2650))
[0080] (compatibility) In order to confirm the compatibility of component (a1) with each phosphate ester, they were mixed in a mass ratio of component (a1):phosphate ester = 80:20, kneaded in the same manner as the kneading method described below, and the appearance was observed.
[0081] When component (b1) was used as the phosphate ester, it was confirmed that the solution was transparent and had high compatibility without any cloudiness.
[0082] When the components (b1'), (b2'), (b3'), (b4'), and (b5') were used as the phosphate esters, white turbidity occurred, and it was confirmed that the compatibility was low.
[0083] <Examples 1 to 7 and Comparative Examples 1 to 9> The materials shown in Tables 2 to 4 were prepared as the constituent materials of the target cellulose-based resin composition. Next, the constituent materials were thoroughly mixed by hand mixing in the blending ratios shown in Tables 2 to 4. The resin materials were previously dried at 80°C for 5 hours. The ratio of component (a1) and component (b1) is the ratio (mass%) to the total of 100 mass% of component (a1) and component (b1). The content of component (c1) is the ratio (mass%) to the total of 100 mass% of components (a1), (b1) and (c1). The blending amount of component (d1) is the ratio based on 100 parts by mass of components other than the colorant, and is expressed in phr.
[0084] (Mixing method) The mixture was fed into a co-rotating twin screw extruder (STEER, product name: Omega30H [φ30, L / D=60]), kneaded at 200°C and 120 rpm, cooled with water, recovered, and pelletized. The pellets were dried at 80°C for 5 hours.
[0085] <Processing stability (extrusion stability of kneaded material)> The stability of the strands of the resin composition discharged from the discharge port of the extruder was evaluated.
[0086] The evaluation criteria are as follows: ◯: Strands are discharged stably. △: Strands are discharged but pulsating. ×: Strands were discharged, but the pulsation was so large that they could not be taken up.
[0087] (Preparation of combustion test specimen: Evaluation specimen 1) The obtained pellets were dried again at 80° C. for 5 hours immediately before molding, and used to produce a molded body (evaluation sample 1) having the following shape using an injection molding machine (manufactured by Toshiba Machine, product name: EC20P).
[0088] Molded body: Length 125mm, width 13mm, thickness 3.2mm, At that time, the molding conditions were set as follows: Molding machine cylinder temperature: 190-230℃ Mold temperature: 60-70℃ Holding pressure: 60-100MPa
[0089] The obtained evaluation sample 1 was used to carry out the following measurements.
[0090] <Flammability test (UL94V test)> Flammability tests were conducted in accordance with the UL94 test (flammability test for plastic materials for equipment parts) established by Underwriters Laboratories after leaving the test specimen (evaluation sample 1) obtained by injection molding for 48 hours in a temperature-controlled room at a temperature of 23°C and humidity of 50%. UL94V is a method for evaluating flame retardancy based on the burning time and dripping property after applying a burner flame (20±1mm flame) to the bottom end of a test specimen of a specified size held vertically for 10 seconds, and is classified into the classes shown in Table 1 below.
[0091] [Table 1]
[0092] The flame retardancy ranking from best to worst is V-0, V-1, V-2. However, materials that do not fall into any of the V-0 to V-2 rankings (low flame retardancy) are classified as V- non-compliant.
[0093] The flaming burning time is the length of time that the test specimen continues to burn with a flame after the ignition source (burner) is removed, where t1 is the burning time after the first flame contact, t2 is the burning time after the second flame contact, and t3 is the afterglow (flameless burning) time after the second flame contact. The second flame contact is performed by immediately contacting the test specimen with the burner flame for 10 seconds if the flame goes out after the first flame contact. The ignition of cotton by dripping is determined by whether the cotton used for marking, located 300±10 mm below the bottom end of the test specimen, is ignited by dripping from the test specimen.
[0094] <Measurement of brightness> The lightness of the obtained evaluation sample 1 was measured by reflection measurement using the SCI method (including regular reflection light) using a spectrophotometer (manufactured by Konica Minolta, product name: spectrophotometer CM-3700A, conforming to JIS Z 8722 condition c, ISO7724 / 1, CIE No.15, ASTM E1164, DIN5033 Teil7). The measurement diameter / illumination diameter was SAV: 3x5mm / 5x7mm. The reflection measurement conditions were di: 8°, de: 8° (diffuse illumination, 8° direction light reception), the field of view was 10°, the light source was a D65 light source, and the UV condition was 100% Full. Here, lightness refers to L* in the CIE1976 L*a*b* color space. The lower the lightness value, the better the jet blackness. The lightness was measured for a sample containing a colorant (d1) (Table 2). The values based on Comparative Example 1 are shown in Table 2.
[0095] (Preparation of sample for haze measurement: Evaluation sample 2) The obtained pellets were dried again at 80°C for 5 hours immediately before molding, and used to produce a molded body (evaluation sample 2) having the following shape using a hot press molding machine (manufactured by Tester Sangyo, product name: SA-303-II-S).
[0096] Molded body: Disk-shaped molded body with a diameter of 50 mm and a thickness of 500 μm At that time, the molding conditions were set as follows: Set temperature: 210℃ Pressure: 10MPa
[0097] The obtained evaluation sample 2 was used to carry out the following measurements.
[0098] <Haze measurement> The haze (cloudiness) of the obtained evaluation sample 2 was measured with a haze meter (manufactured by Murakami Color Research Laboratory, product name: HM-65W type, conforming to JIS K 7136). A D65 light source was used.
[0099] The results are shown in Tables 2 to 4.
[0100] [Table 2]
[0101] Comparative Example 3 had poor processing stability, and it was not possible to prepare an evaluation sample for measuring flame retardancy and brightness.
[0102] [Table 3]
[0103] [Table 4]
[0104] Although the present invention has been described above with reference to the embodiments and examples, the present invention is not limited to the above-mentioned embodiments and examples. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention.
[0105] A part or all of the above embodiments may be described as follows, but the disclosure of the present application is not limited to the following supplementary notes.
[0106] (Appendix 1) Component (A): Cellulose acetate, Component (B): one or more phosphate esters selected from the group consisting of triphenyl phosphate, triethyl phosphate, tributyl phosphate, and tricresyl phosphate; Component (C): Anti-drip agent, Including, The content of component (B) is 25% by mass or more and 30% by mass or less relative to 100% by mass of the total content of components (A) and (B), A cellulose-based resin composition, in which the content of component (C) is 0.01% by mass or more, preferably 0.1% by mass or more and 1% by mass or less, relative to the total content of components (A), (B) and (C) being 100% by mass.
[0107] (Appendix 2) 2. The cellulose-based resin composition according to claim 1, wherein the component (B) comprises triphenyl phosphate.
[0108] (Appendix 3) 3. The cellulose-based resin composition according to claim 1, wherein the component (C) comprises a fluorine-based anti-drip agent.
[0109] (Appendix 4) 4. The cellulose resin composition according to any one of claims 1 to 3, wherein the component (C) comprises polytetrafluoroethylene.
[0110] (Appendix 5) 5. The cellulose-based resin composition according to any one of claims 1 to 4, wherein a molded article having a thickness of 500 μm formed from the resin composition containing no colorant has a haze value of 35% or less.
[0111] (Appendix 6) 6. The cellulose resin composition according to any one of claims 1 to 5, further comprising a colorant.
[0112] (Appendix 7) 7. The cellulose-based resin composition according to claim 6, wherein the colorant is carbon black.
[0113] (Appendix 8) 8. The cellulose resin composition according to claim 7, wherein the carbon black is acidic carbon black.
[0114] (Appendix 9) A molded article formed using the cellulose resin composition according to any one of claims 1 to 8.
[0115] This application claims priority based on Japanese Patent Application No. 2021-124854, filed on July 29, 2021, the disclosure of which is incorporated herein in its entirety.
[0116] Although the present invention has been described above with reference to the embodiments and examples, the present invention is not limited to the above-mentioned embodiments and examples. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention.
Claims
1. A cellulose-based resin composition comprising: Component (A): Cellulose acetate, Component (B): one or more phosphate esters selected from the group consisting of triphenyl phosphate, triethyl phosphate, tributyl phosphate, and tricresyl phosphate; Component (C): an anti-drip agent; Including, The content of component (B) is 25% by mass or more and 30% by mass or less relative to 100% by mass of the total content of components (A) and (B), the content of the component (C) is 0.01% by mass or more and 1% by mass or less relative to 100% by mass of the total content of the components (A), (B) and (C); A cellulose-based resin composition containing no colorant, wherein a molded article having a thickness of 500 μm is formed from the cellulose-based resin composition and has a haze value of 35% or less.
2. The cellulose-based resin composition according to claim 1 , wherein the component (B) comprises triphenyl phosphate.
3. The cellulose-based resin composition according to claim 1 or 2, wherein the component (C) comprises a fluorine-based anti-drip agent.
4. The cellulose-based resin composition according to claim 1 or 2, wherein the component (C) comprises polytetrafluoroethylene.
5. The cellulose resin composition according to claim 1 or 2, further comprising a colorant.
6. The cellulose-based resin composition according to claim 5 , wherein the colorant is carbon black.
7. The cellulose-based resin composition according to claim 6, wherein the carbon black is an acidic carbon black.
8. A molded article formed using the cellulose resin composition according to claim 1 or 2.
Citation Information
Patent Citations
High-transparency flame-retardant cellulose material and preparation method thereof
CN108359138A
Soil fungicide
JP1987039504A
Resin composition, molded product, electrical product, and method for producing the resin composition
JP2005162871A
Resin composition and molding comprising the same
JP2006111858A
Resin composition, resin composition for injection molding, molded article, and housing for electric / electronic device
JP2011225841A